Thin plate model for transverse mode analysis of surface acoustic wave devices. (10th June 2016) - Tang, Gongbin; Han, Tao; Chen, Jing; Zhang, Benfeng; Omori, Tatsuya; Hashimoto, Ken-ya
Abstract: In this paper, we propose a physical model for the analysis of transverse modes in surface acoustic wave (SAW) devices. It is mostly equivalent to the scalar potential (SP) theory, but sufficiently flexible to include various effects such as anisotropy, coupling between multiple modes, etc. First, fundamentals of the proposed model are established and procedures for determining the model parameters are given in detailed. Then the model is implemented in the partial differential equation mode of the commercial finite element analysis software COMSOL. The analysis is carried out for an infinitely long interdigital transducer on the 128°YX-LiNbO3 substrate. As a demonstration, it is shown how the energy leakage changes with the frequency and the device design.